A simple simulation-derived descriptor for the deposition of polymer-wrapped carbon nanotubes on functionalized substrates. Issue 25 (15th June 2022) - Shen, Zhizhang; Dwyer, Jonathan H.; Sun, Jian; Jinkins, Katherine R.; Arnold, Michael S.; Gopalan, Padma; Van Lehn, Reid C.
Abstract : Analysis of solvent structure obtained from all-atom molecular dynamics simulations reveals a descriptor that predicts the experimental deposition of polymer-wrapped carbon nanotubes. Abstract : Controlling the deposition of polymer-wrapped single-walled carbon nanotubes (s-CNTs) onto functionalized substrates can enable the fabrication of s-CNT arrays for semiconductor devices. In this work, we utilize classical atomistic molecular dynamics (MD) simulations to show that a simple descriptor of solvent structure near silica substrates functionalized by a wide variety of self-assembled monolayers (SAMs) can predict trends in the deposition of s-CNTs from toluene. Free energy calculations and experiments indicate that those SAMs that lead to maximum disruption of solvent structure promote deposition to the greatest extent. These findings are consistent with deposition being driven by solvent-mediated interactions that arise from SAM-solvent interactions, rather than direct s-CNT-SAM interactions, and will permit the rapid computational exploration of potential substrate designs for controlling s-CNT deposition and alignment.